Investigating of rain attenuation impact on Free Space Optics propagation in tropical region - Ahmad Zabidi, Suriza; Islam, Md. Rafiqul; Mohammed Al-Khateeb, Wajdi Fawzi; Naji, Ahmed Wathik (2011)
Free Space Optics (FSO) is an emerging technology in the area where higher speed and larger bandwidth is required. Technologically, FSO is similar to communication using fiber optic cables. Since the two technologies are similar, they share the same advantages such as higher speed, unlimited bandwidth and protocol independent. However, in term of cost and time for deployment, the cost to deploy FSO is cheaper and the deployment time is shorter since no cable is needed for FSO so the time and cost is reduce significantly. Although FSO has all the advantages of the best quality as communication medium, local weather condition is the drawback of FSO link performance. The aim of this paper is to investigate on this limitation with the focus on atmospheric attenuation on the propagation of FSO signal. General atmospheric attenuation will be discussed and the focus will be on rain. The motivation of this is to develop attenuation model that best represent tropical weather condition.